Exploration Of Children's Activities In The Deli River Slum Area, Medan - Rangga Wardhana Barus; Wahyuni Zahrah (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
The problem that occurs in Medan city is the existence of riverside slum settlements, one of which is Aur village. The irregularity of buildings, high building density level, and the quality of buildings and facilities and infrastructure that do not meet the requirements for adequate housing can affect children's development. This research aims to explore children's activities in riverside slum areas. The research method used is exploratory qualitative, namely in the form of interviews and observations. The results of the research show that children spend their time in the afternoon playing and reciting the Koran around Masjid Jami Aur. This shows that the mosque and its courtyard are an important space for children's activities.